Customer Complaint Behaviour and Intentions in Mobile Telecommunication Services - Umar, Amina Aliyu (2011)
Complaints are a form feedback from customers which when used effectively by a service provider can result in an improvement of its services (Hart et al, 1990; Kim et al, 2003; Slater and Narver, 1995; Soderlund, 1998).In light of the importance of mobile telecommunications service therefore, the objectives of this research are to examine the dissatisfaction responses amongst telecommunication services consumers in Malaysia and to explore whether male and female consumers differ in their complaint action choices. The study examines the actions that consumers engage in when they are dissatisfied with the services of their mobile telecommunication operators and the behaviour intended to engage in the event of a dissatisfactory experience. Data for the study was collected through an online survey questionnaire from 141 customers of various telecommunication services in Malaysia. The results show that consumers would rather converse with friends and family when they are dissatisfied than discuss the issue directly with the service provider. This behaviour is unfavourable to telecommunications operators because they are likely to be ignorant of customer grievances and as such cannot resolve the grievances or improve their service offerings in the long run. These companies also run the risk of customers’ exiting to other providers. The findings of the study also showed that in the event of a dissatisfaction episode in future, customers are also not likely to consider communicating directly with their provider. The results also showed that there was no gender difference in the complaint intentions of consumers.